Mutant of Escherichia coli deficient in osmoregulation of periplasmic oligosaccharide synthesis. - Clark, D P (1985)
A mutant of Escherichia coli (mdoR) has been isolated which is defective in synthesis of the membrane-derived oligosaccharides (MDO) normally found in the periplasmic space. In media of high osmotic pressure this defect is suppressed and MDO levels approaching those of the wild type are produced. The mdoR mutant also fails to accumulate glycogen; however, genetic analysis showed that mdoR was not cotransducible with the known glg (glycogen) locus. A further relationship between MDO and glycogen metabolism was suggested by two observations that (i) certain glg mutants affect MDO accumulation and (ii) elevated osmotic pressure inhibits glycogen accumulation, in both wild-type and mdoR cells.